Human oncoprotein MDM2 activates the Akt signaling pathway through an interaction with the repressor element-1 silencing transcription factor conferring a survival advantage to cancer cells - Singh, S (Nature Publishing Group, 2013)
The current paradigm states that the Akt signaling pathway phosphorylates the human oncoprotein mouse double minute 2 (MDM2), leading to its nuclear translocation and degradation of the tumor suppressor p53. Here we report a novel Akt signaling pathway elicited by MDM2. Upregulation of endogenous MDM2 promotes, whereas its downregulation diminishes, Akt phosphorylation irrespective of p53 status. MDM2 requires phosphatidylinositol (PI)3-kinase activity for enhancing Akt phosphorylation and upregulates this activity by repressing transcription of the regulatory subunit p85 of PI3-kinase. MDM2 interacts with the repressor element-1 silencing transcription factor (REST), a tumor suppressor that functions by downregulating PI3-kinase activity and Akt phosphorylation, prevents localization of REST on the p85 promoter and represses p85 expression. The deletion mutant of MDM2 capable of upregulating Akt phosphorylation represses p85 expression and interferes with localization of REST on the p85 promoter, whereas the deletion mutant of MDM2 that does not increase Akt phosphorylation cannot perform these functions. Silencing of REST abrogates the ability of MDM2 to upregulate Akt phosphorylation and downregulate p85 expression, implicating the ability of MDM2 to interact with REST in its ability to inhibit p85 expression and activate Akt phosphorylation. Inhibition of MDM2-mediated Akt phosphorylation with an Akt-phosphorylation-specific inhibitor abrogates its ability to improve cell survival. Consistently, the Akt phosphorylation function of MDM2 was required for its ability to improve cell survival after treatment with a chemotherapeutic drug. Our report not only unravels a novel signaling pathway that contributes to cell survival but also implicates a p53-independent transcription regulatory function of MDM2 in Akt signaling.